Spinal trauma in children - Roche, Claire; Carty, H. (Pediatric radiology, 2001)
Evaluation of the child with suspected spinal injury can be a difficult task for the radiologist. Added to the problems posed by lack of familiarity with the normal appearances of the paediatric spine is anxiety about missing a potentially significant injury resulting in neurological damage. Due to differences in anatomy and function, the pattern of injury in the paediatric spine is different from that in the adolescent or adult. Lack of appreciation of these differences may lead to over investigation and inappropriate treatment. This review attempts to clarify some of the problems frequently encountered. It is based on a review of the literature as well as personal experience. The normal appearances and variants of the spine in children, the mechanisms and patterns of injury are reviewed highlighting the differences between children and adults. Specific fractures, a practical scheme for the assessment of spinal radiographs in children, and the role of cross sectional imaging are discussed.